Role of ?-Catenin and its mechanosensing properties in regulating Hippo/YAP-dependent tissue growth. - Sarpal, R.; Yan, V.; Kazakova, L.; Sheppard, L.; Yu, J.C.; Fernandez-Gonzalez, R.; Tepass, U. (PLoS Genetics, 2019)
?-catenin is a key protein of adherens junctions (AJs) with mechanosensory properties. It also acts as a tumor suppressor that limits tissue growth. Here we analyzed the function of Drosophila ?-Catenin (?-Cat) in growth regulation of the wing epithelium. We found that different ?-Cat levels led to a differential activation of Hippo/Yorkie or JNK signaling causing tissue overgrowth or degeneration, respectively. ?-Cat can modulate Yorkie-dependent tissue growth through recruitment of Ajuba, a negative regulator of Hippo signaling to AJs but also through a mechanism independent of Ajuba recruitment to AJs. Both mechanosensory regions of ?-Cat, the M region and the actin-binding domain (ABD), contribute to growth regulation. Whereas M is dispensable for ?-Cat function in the wing, individual M domains (M1, M2, M3) have opposing effects on growth regulation. In particular, M1 limits Ajuba recruitment. Loss of M1 causes Ajuba hyper-recruitment to AJs, promoting tissue-tension independent overgrowth. Although M1 binds Vinculin, Vinculin is not responsible for this effect. Moreover, disruption of mechanosensing of the ?-Cat ABD affects tissue growth, with enhanced actin interactions stabilizing junctions and leading to tissue overgrowth. Together, our findings indicate that ?-Cat acts through multiple mechanisms to control tissue growth, including regulation of AJ stability, mechanosensitive Ajuba recruitment, and dynamic direct F-actin interactions.